An assessment of urban residents' knowledge and appreciation of the intangible benefits of trees in two medium sized towns in South Africa - Chinyimba, Abby (Rhodes University, Faculty of Science, Department of Environmental Science, 2013)
In order to meet the different public needs and requirements of contemporary urban society, a better understanding of public perceptions, appreciation and knowledge of the assorted values derived from urban trees is beneficial for improved urban greening. Thus, this study carried out an assessment of urban residents' knowledge and appreciation of the benefits of trees and the role they play in enhancing the quality of life in urban systems. The study primarily focused on the intangible benefits (also referred to as cultural and regulating services) of urban trees, because most research to date in South Africa on trees and the benefits derived from them is biased towards the provisioning services of trees in rural areas. The significance and contribution of the intangible benefits of trees in urban systems is often underestimated and not seriously taken into account by urban planners, policy makers and other key decision makers. The study was conducted in three different residential settlement types (formal townships, RDP settlements and informal settlements) in two towns in the Limpopo Province in South Africa, namely Bela-Bela and Tzaneen. Findings revealed that the intangible benefits of trees are seen to play a significant role in improving both residents' quality of life and the environmental conditions in cities, including the preservation of biodiversity. Findings also showed that urban residents had strong spiritual connections with trees and placed considerable cultural and historical importance on specific tree species and individual trees. Urban residents in both towns had moderate knowledge of the intangible benefits of trees based on the knowledge score that was created for the purposes of this study. Fifty seven percent of the residents had 'reasonable' knowledge of some of the intangible benefits of trees, while 43% had low levels of knowledge. That said, the majority of residents demonstrated high appreciation (98%) of the intangible benefits of trees (especially social and cultural values), with few residents not recognising these, suggesting that knowledge does not necessarily lead to appreciation. Age and level of education were found to influence knowledge of the intangible benefits of trees. A large proportion (86%) of residents who possessed tertiary level qualifications had more knowledge of the intangible benefits of trees as compared to residents with no formal education. Findings also revealed that younger respondents (60%) had more knowledge of the intangible benefits of trees. Factors that influenced appreciation of the intangible benefits of trees included links to crime, peoples' value systems (their pro-environmental and altruistic values) and residential settlement type. Sixty five percent of residents in both towns felt that urban street trees and trees in public spaces attract criminals and promote crime, while 67% of RDP and 96% of informal township residents did not use or appreciate the social and recreational benefits of trees mainly because of the absence or long distances to public parks. A Willingness To Pay (WTP) survey revealed that a high proportion of residents in Bela-Bela (86%) were WTP a small annual fee in order to sustain greening initiatives in their communities compared to the residents in Tzaneen (53%). In terms of the planting and retention of trees, it was found that 300 households in both study towns had planted and retained a total of 1 615 trees in spite of the various factors that negatively influenced planting and retention of trees such as residency time and tenure security. The majority (66%) of informal township residents said tenure security was an important factor to consider when making tree planting decisions, while this was not an issue for formal township and RDP residents. Policy implications and recommendations are presented to help municipalities and urban planners improve and develop effective policies and programmes that will enable implementation of sustainable urban greening programmes
Keywords: Trees in cities -- South Africa--Limpopo; Cities and towns -- South Africa -- Limpopo; Ecology -- South Africa -- Limpopo; Human-plant relationships -- South Africa -- Limpopo; Plants and civilization -- South Africa -- Limpopo; Willingness to pay -- South Africa -- Limpopo; Limpopo (South Africa) -- Environmental conditions; Cultural importance; Cultural and regulating services; Intangible benefits; Urban systems